The Determinants of HIV Infection and Related Sexual Behaviors : Evidence from Lesotho - Corno, Lucia (World Bank, Washington, DC, 2012)
This paper analyzes the socioeconomic determinants of HIV infection and related sexual behaviors using the 2004 Lesotho Demographic and Health Survey. The authors find that in Lesotho education appears to have a protective effect: it is negatively associated with HIV infection (although not always significantly) and it strongly predicts preventive behaviors. The findings also show that married women who have extra-marital relationships are less likely to use a condom than non-married women. This is an important source of vulnerability that should be addressed in prevention efforts. The paper also analyzes HIV infection at the level of the couple. It shows that in 41 percent of the infected couples, only one of the two partners is HIV infected. Therefore, there are still opportunities for prevention inside the couple.